The Effect of Digital Problem Solving Therapy on Quality of Life in Pregnant Women Who Are Victims of Domestic Violence - Putri, Dian Priharja; Lindayani, Linlin; Mutiar, Astri; Darmawati, Irma (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aim: This study aims to determine the effect of digital problem-solving therapy (DPST) on the quality of life (QOL) of pregnant women who are victims of domestic violence. Methods: The research was conducted using a quasi-experimental design with two groups: an intervention group receiving digital problem-solving therapy and a control group receiving standard care. The study took place over three months at the National Commission on Violence Against Women service centers and referral hospitals in Bekasi City, West Java. The intervention involved four sessions per month focusing on psychological well-being and QOL. A total of 100 pregnant women participated, meeting the criteria of being over three months pregnant, having experienced domestic violence, owning a smartphone, and living with their husbands. Results: The results showed a statistically significant increase in QOL scores within the intervention group after the therapy, with a t-score of 13.76 and a p-value of 0.001. Additionally, the intervention group exhibited a larger improvement in QOL at post-test compared to the control group (ß = 8.20, p < 0.001). Conclusion: Digital problem-solving therapy significantly improves the quality of life of pregnant women experiencing domestic violence. Future studies should explore the effectiveness of this intervention among more diverse research groups, focusing on participants with varied mental health and psychological characteristics.